Environmental contaminants in human milk - ANDERSON, HENRY A; WOLFF, MARY S (Journal of exposure analysis and environmental epidemiology, 2000)
Environmental contaminants can be stored in the mother's body or can be transiently present from current diet, occupational exposures or personal habits. These chemicals can be transferred prenatally to the developing fetus or postnatally from breast milk to the nursing infant. Exposures through breast milk can be substantial, especially when the mother has significant ongoing exposures or has accumulated an unusually high body burden of persistent chemicals. Several studies demonstrate that organochlorines (OCs) acquired from breast milk elevate a child's body burden for several years. The decline of persistent OC residues in Western countries suggests that these exposures through breast milk will also diminish. Heavy metals such as lead and mercury are also present in milk, but the pharmacokinetics are quite different from OCs. Less persistent environmental agents, including solvents, polycyclic aromatic hydrocarbons, certain pesticides, and nicotine, can also be detected in milk. There is little information on currently used pesticides and other more recently identified environmental agents for which exposures are common today. Epidemiologic research has established that pre- and postnatal exposures to environmental contaminants including lead and OCs are associated with developmental deficits in early childhood. Therefore, characterization of these contaminants in breast milk can add to our knowledge of potential environmental exposures among children.